Barreiras e facilitadores na implantação do business intelligence para contabilidade - Fernandes, Aline Araújo (2023)
The study aimed to identify how the factors classified as "barriers" and/or "facilitators" work during the implementation of a Business Intelligence (BI) system in a company that provides accounting services, through the lens of the Theory of Diffusion of Innovation. The research contributes with professionals and students in the accounting area, pointing out updates of the procedures carried out by the profession through technological tools, and contributes with the academic universe by portraying the reality of the adoption of new information systems, identifying through the Diffusion Theory of Innovation, the barriers and/or facilitators that permeate this process. The study is objectivist, positivist and qualitative, having its constructs previously established from the study by Hornik (2004), and using the Theory of Diffusion of Innovation by Rogers (1983). Action research was used as a strategy. Primary evidence consisting of semi-structured interviews to be carried out with the participants and a field diary were used. The research participants were the owner of the company providing accounting services, the employee of the company providing accounting services and the client user of the accounting information, represented by the organization's controller. The results demonstrated the factors that represented barriers and/or influential facilitators in each of the stages of the implementation process of an accounting technological innovation. The identified facilitators were: openness to changes and access to information derived from insertion in a social network in the knowledge stage; need for achievement in the knowledge, persuasion and decision stages; persuasion in the persuasion stage; normative pressure derived from insertion in a social network in the stages of persuasion and decision; benefits or costs in the persuasion, decision and confirmation stages; income and wealth at the decision stage; communication skills in the implementation and confirmation stages; relative advantage in the implementation and confirmation stages; experimentability, facility to the distribution and communication system and empathy in the implementation stage; and compatibility in the confirmation step. The identified barriers were: impulses and benefits or costs in the persuasion stage; persuasion in the persuasion and implementation stages; and compatibility and complexity at the implementation stage. The results also demonstrated the process of selection and construction of a total of 21 indicators about liquidity; solvency; capital composition; asset recoverability; representativeness of liabilities; representativeness of costs; representativeness of revenues; personnel expenses; and profitability. Finally, the results brought reflections on the process of adopting accounting innovations, through the detection of the following deficiencies in the process of implementing the tool involving the following points: adjustment of informational processes; learning process of accounting professionals; directing the efforts of accounting professionals to accounting information; and generation of predictive information.